Analysis of Modeling of Current Differential Protection - Denis B. Solovev; Angelina I. Makeeva (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Analysis of transients in longitudinal differential protection schemes is given basing on results obtained by simulation. Simulation diagram for modeling differential protection with current transformers with non-linear cores is proposed. Main shortcomings of using current transformers as measuring transducers are shown. Solutions of the problem revealed are proposed.